Curriculum Management at Insan Robbani - Wijaya, Imam Agung (Journal of Advanced Islamic Educational Management, 2024)
This study aims to analyze the management of Islamic religious education curriculum at Insan Robbani IT Junior High School in North Lampung, including the planning, implementation, and evaluation stages. The research used a qualitative approach with data triangulation through in-depth interviews, observation, and document analysis. The results show that the success of curriculum management is supported by regular evaluation of the previous curriculum, the formation of a curriculum development team involving various stakeholders, and the integration of Islamic values in learning. Evaluation is conducted holistically, covering academic aspects and student character building. The findings provide an important contribution for integrated Islamic schools in improving the quality of curriculum management to support Islamic values-based education.